(untitled) (Journal of Information Technologies in Education (ITE), 2015)
Rapid development of new information and communication technologies (ICT) and informatization of education places heavy demands on computer science specialists training. Among the most important methodological procedures that conducive to increasing of motivational component of educational process and, as a consequence making it more efficient is the use of visualization. The using of multimedia technology is perspective direction for realization of the didactic visualization principle. By means of visualization of abstract objects and events implemented by computer tools, had been elevated level of perception complicated educational material, ensured its optimal learning and memorizing by students. The article considers issues improvement the course of Cryptology training at higher school by tools of computer animation based on flash-technology. The practicability using multimedia applications both at the explanation of new material, and in the course of independent work of students is given. The introduction of computer animation of cryptographic algorithms based on flash-technology in the educational process activates the cognitive function of students and develops their interest to the subject. Has been proposed demonstrate cryptographic algorithms with accompaniment of animated flash-presentations based on CrypTool 1